PSYCHOLINGUISTIC FACTORS AFFECTING THE UNDERSTANDING OF SPECIALIZED TERMS BY TRANSLATORS - G‘afurova Nazokat Bakhriddin’s daughter; Abdullayeva Nafisa Bakhriddin’s daughter (Ustozlar uchun, 2025)
Annotation: This article investigates the psycholinguistic factors that influence the comprehension of specialized terms by translators. It discusses how cognitive processes such as memory, attention, prior knowledge, and conceptual mapping affect the accurate understanding and rendering of domain-specific terminology. Drawing on examples from scientific, legal, and technical texts, the paper highlights common barriers to terminological understanding, including unfamiliarity with field-specific concepts, cognitive overload, and ambiguous lexical structures. Recommendations are made for translator training programs to incorporate psycholinguistic awareness and cognitive strategy development.